2007
DOI: 10.1017/s0033291707000578
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen, menstrual cycle phases, and psychopathology in women suffering from schizophrenia

Abstract: The present findings indicate that estradiol may have specific antipsychotic-like effects on the symptoms of schizophrenia. Thus further investigation into the therapeutic effect of estrogen may be worthwhile.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
65
3
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(77 citation statements)
references
References 62 publications
8
65
3
1
Order By: Relevance
“…Also, Bergemann et al [32] found a significant effect of the menstrual cycle phase and 17-β-estradiol levels on positive and negative symptoms of 125 women with schizophrenia and related psychoses. The same authors [33] could furthermore show a significant effect of estrogen on the comprehension of metaphoric speech and/or concretism, a main feature of schizophrenic thought and language disturbance.…”
Section: Clinical Findingsmentioning
confidence: 99%
“…Also, Bergemann et al [32] found a significant effect of the menstrual cycle phase and 17-β-estradiol levels on positive and negative symptoms of 125 women with schizophrenia and related psychoses. The same authors [33] could furthermore show a significant effect of estrogen on the comprehension of metaphoric speech and/or concretism, a main feature of schizophrenic thought and language disturbance.…”
Section: Clinical Findingsmentioning
confidence: 99%
“…The second incidence peak in women after menopause is in line with this suggestion. Indeed, female patients with schizophrenia in the low estrogen phase of their menstrual cycle have more severe symptoms (Grigoriadis and Seeman, 2002), and studies controlling for estrogen plasma levels demonstrate a negative correlation between 17β-estradiol levels and severity of schizophrenia symptoms in women (Gattaz et al, 1994;Riecher-Rössler et al, 1994;Bergemann et al, 2007), as well as in men (Kaneda and Ohmori, 2005). In a previous review article, we performed a meta-analysis of five randomized controlled trials (RCTs) on the efficacy of estrogen augmentation in premenopausal women with schizophrenia and found a significant mean effect on total, positive, and negative symptom severity (Begemann et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Hormone levels were assessed in the follicular, peri-ovulatory, and luteal phases of the menstrual cycle. Significant improvement in psychotic, but not depressive, symptoms (as measured by scores on the Positive and Negative Syndrome Scale and the Brief Psychiatric Rating Scale) was observed during the luteal (high estrogen) phase, compared with the other menstrual phases (32). Unexpectedly, no difference was found between the follicular and the peri-ovulatory phase, suggesting the probable contribution of progesterone to symptom improvement.…”
Section: Schizophrenia and Menstruation -More Recent Studiesmentioning
confidence: 87%